PENGARUH MODIFIKASI PERMAINAN GOBAK SODOR TERHADAP KEMAMPUAN MOTORIK KASAR SISWA KELAS III SDN PAKINTELAN 03 TAHUN AJARAN 2025 - Fadhil Humam `Azi; Agus Pujianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of modifying the traditional gobak sodor game on the gross motor skills of grade III students at SDN Pakintelan 03. A quantitative approach was employed using a pre-experimental design with a one-group pretest-posttest model. The subjects consisted of 25 students. Data collection instruments included gross motor skill tests such as the 4x10 meter Shuttle Run, tennis ball throw-and-catch test, Stork Stand balance test, and 30-meter sprint. The analysis results indicated a significant improvement in gross motor scores after the treatment. The t-test results showed a significance value (2-tailed) of 0.060 > 0.05, indicating that the Gobak Sodor game had a significant effect on improving students’ gross motor skills.